Metaphor is Generic - VOGEL, CARL (My University, 2008)
An approach to sense extension tailored for polysemy associated with non-literal language expanded to include belief revision generally. The relationship between metaphor and genericity as rhetorical devices is discussed, and both are accounted for as related species within the same framework of dynamic semantics. The theoretical apparatus is related to a dominant theory of metaphor interpretation and processing which holds metaphorical utterances to be class inclusion statements involving dual reference for the the metaphorical vehicle.
Proceedings of LREC
Sentiment Analysis: Emotion, Metaphor, Ontology and Terminology EMOT 2008
PUBLISHED
Marrakech, Morocco
Keywords: Computer Science; Digital Humanities; Intelligent Content & Communications; Computational linguistics